ОСОБЕННОСТИ РАБОТЫ НИЗКОВОЛЬТНЫХ ЛОКАЛЬНЫХ СЕТЕЙ В НЕПОЛНОФАЗНЫХ И АВАРИЙНЫХ РЕЖИМАХ - Жаркин, А.Ф.; Новский , В.А.; Каплычный , Н.Н.; Козлов , А.В.; Малахатка , Д.А. (Інститут електродинаміки НАН України, Київ, 2012)
Open-phase operating conditions, emergency and post-fault modes of operations of low voltage distributee networks with the local areas of power supply, which fulfilled with artificial neutral point are investigate. Practical recommendations are given on development and use of filters of currents a zero sequence for realization SES with an artificial zero wire. Figures 2.